Increase Dietary Fiber Intake Ameliorates Cecal Morphology and Drives Cecal Species-Specific of Short-Chain Fatty Acids in White Pekin Ducks - Hao, Yongsheng; Ji, Zhanqing; Shen, Zhongjian; Xue, Youjia; Zhang, Bo; Yu, Daxin; Liu, Tong; Luo, Dawei; Xing, Guangnan; Tang, Jing; Hou, Shuisheng; Xie, Ming (Frontiers in Microbiology, 2022)
The current study was to investigate the effects of total dietary fiber (TDF) levels on modulating cecal morphology and the response of microbiota to maintain gut health for duck growth. A total of 192 male White Pekin ducks of 14-days-old were randomly allocated and fed diets containing 12.4%, 14.7% and 16.2% TDF until 35 days under the quantitative feed intake. Each dietary group consisted eight replicates with eight birds each. The results revealed that 14.7% and 16.2% TDF groups significantly promoted growth performance and improved villus height, ratio of villus to crypt, muscle layer thickness and goblet cells per villus of cecum in ducks. qPCR results showed that the transcriptional expression of Claudin-1, Muc2, IGF-1 and SLC16A1 were significantly up-regulated in cecum in 14.7% and 16.2% TDF groups. Meanwhile, the concentrations of IGF-1 and DAO in circulating were significantly increased in 14.7% and 16.2% TDF groups. Furthermore, the concentrations of butyrate, isobutyrate, valerate and isovalerate in cecum were conspicuously improved in 14.7% and 16.2% TDF group while that of propionate was significantly decreased. In addition, the concentration of butyrate, isobutyrate, valerate and isovalerate in cecum presented negative correlations with the concentration of DAO in circulating. 16S rRNA gene sequencing results showed that 14.7% TDF group importantly elevated the microbial richness. Simultaneously, butyrate-producing bacteria like the family Lachnospiraceae, Oscillospiraceae and Erysipelatoclostridiaceae were enriched as biomarkers in 16.2% TDF group. Correlation network analysis revealed that the associations between specific bacteria and short-chain fatty acids (SCFAs) induced by different TDF levels, and the correlations with bacteria. For example, the genus Monoglobus and CHKCI002 showed a positive correlation with butyrate and there was a positively coexistent association between Monoglobus and CHKCI002. In summary, these data revealed that increasing TDF level could enhance the cecal morphology and drive cecal species-specific of SCFAs in ducks.